MATHEMATICAL LITERACY IN ISLAMIC INHERITANCE DISTRIBUTION: FOCUSING IN FRACTIONAL CONCEPTS - Evvy Lusyana (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This mixed-methods diagnostic survey mapped mathematical literacy competencies in Islamic inheritance distribution systems, specifically examining fraction concept application among 36 PGMI students at STIT Muhammadiyah Tempurejo Ngawi who had completed Basic Mathematics MI/SD courses. Data collection utilized a 25-item diagnostic test and clinical interviews, with analysis combining descriptive statistics and Newman's Error Analysis (NEA). Findings revealed: (1) 61% of respondents solved basic fractional calculations in simple inheritance cases; (2) 19% resolved complex cases requiring share adjustments; (3) significant competency gaps existed in heirs identification (58%) and fractional operations (33%). Qualitative analysis identified 72% of students experienced difficulties integrating jurisprudential inheritance rules with mathematical procedures. The study recommends three curricular improvements: (a) strengthening foundational understanding, (b) enhancing contextual fraction operation skills, and (c) embedding authentic inheritance case studies. This provides the first comprehensive baseline profile of Islamic inheritance mathematics literacy among PGMI students and informs Sharia-contextualized curriculum development at STIT Muhamamdiyah Tempurejo Ngawi.